2020
DOI: 10.3390/diagnostics10090669
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity, Specificity and Predictive Values of Molecular and Serological Tests for COVID-19: A Longitudinal Study in Emergency Room

Abstract: Background: We assessed the sensitivity, specificity and positive and negative predictive value (PPV and NPV) of molecular and serological tests for the diagnosis of SARS-CoV-2 infection. Methods: A total of 346 patients were enrolled in the emergency room. We evaluated three Reverse Transcriptase-real time PCRs (RT-PCRs) including six different gene targets, five serologic rapid diagnostic tests (RDT) and one ELISA. The final classification of infected/non-infected patients was performed using Latent Class An… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 41 publications
1
45
0
Order By: Relevance
“…First, we treat all positive tests as true positive. While errors may occur, the rate of false-positive results is very low 25 and we do not expect it to significantly affect our results. Future studies can further improve the reliability of confirmation of positive cases by combining PCR test results with serology tests.…”
Section: Discussionmentioning
confidence: 76%
“…First, we treat all positive tests as true positive. While errors may occur, the rate of false-positive results is very low 25 and we do not expect it to significantly affect our results. Future studies can further improve the reliability of confirmation of positive cases by combining PCR test results with serology tests.…”
Section: Discussionmentioning
confidence: 76%
“…An analysis of data from seven longitudinal studies found that the probability of false negatives of RT-PCR tests reached their lowest value of 20% on the third day after onset of symptoms before starting to increase again [13]. An Italian study of multiple RT-PCR tests that targeted different genes of viral RNA used a repeated testing design in the emergency room and reported sensitivity values ranging from 62% to 94% [4]. It was not clear whether they studied a test that may be considered equivalent to the Chinese test, but the range of reported sensitivity values includes the point estimate and error interval that was estimated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Accurate and sensitive measurement of virus-specific antibodies could complement diagnostic testing, provide information about the true prevalence of infection, provide insight into anti-viral immunity, and help assess vaccine responses. However, a lack of required sensitivity and specificity of many of the SARS-CoV-2 antibody tests available to date have led some to conclude that they have limited clinical utility in combating COVID-19 31 . Here, we present a modified ELISA protocol with exceptional sensitivity with high concentration samples that enables the detection of low levels of antigen-specific antibodies in human specimens.…”
Section: Discussionmentioning
confidence: 99%